Experimental Studies of Sliding Bearings of Locomotive Turbochargers by Their Level of Vibration - Pogrebnyak, Andrii; YÐµvtushenko, Andrii; Ðšravets, Andrii; Kovtunenko, Artem; Tilichko, Igor (International Journal of Engineering and Technology, 2018)
The diagnostic features and sources of vibration of sliding bearings of diesel locomotive turbochargers (disappearance of the negative allowance on bearing bushings, self-oscillation in the bearing, self-oscillation when the negative allowance on the bearing bushing disappears, excitation of blade harmonics, etc.) are described in brief. The results of experimental studies of diesel locomotive turbochargers equipped with cylindrical and elliptical sliding bearings are shown. The specific spectra of vibration velocity of the bearing housings (cylindrical and elliptical) in the low-frequency range are presented. Bearing frequencies have been detected in the low-frequency vibration spectrum of the turbocharger housing with cylindrical bearings, and the connection of the detected diagnostic features with defects in sliding bearings has been established. Blade frequencies of the compressor and turbines on turbochargers with cylindrical and elliptical sliding bearings have been found in the high-frequency part of the vibration spectrum. These frequencies are necessary for identifying rotor harmonics and bearing frequencies. It has been established that for a defect-free bearing of turbochargers with elliptical and cylindrical sliding bearings, the vibration velocity of the rotor harmonics and the bearing frequency should not exceed the rated values.
Keywords: blade harmonics; frequency bands; low-frequency spectrum; self-oscillations; sliding bearings; turbocharger; vibration velocity.